2022
DOI: 10.1016/j.ssmph.2021.100999
|View full text |Cite
|
Sign up to set email alerts
|

Home confinement and mental health problems during the Covid-19 pandemic among the population aged 50 and older: A gender perspective

Abstract: Home confinement during the Covid-19 pandemic is usually associated with worsening mental health. In the case of older adults, although they have been identified as a vulnerable group in terms of mental health, the results of studies on the relationship between home confinement and mental health are not consistent and few studies have adopted a gender perspective. Using data from the SHARE Corona Survey (2020), we aimed to analyse the role of gender on the relationship between home confinement and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…This study also highlights that economic stability of Portuguese citizens weakened during the pandemic of COVID-19 and shows that there is significantly evidence that agreement with the maintenance of the citizens’ economic stability increases with economic stability before the pandemic. These findings are in accordance with those of Andrade et al [ 41 ] that showed that the pandemic has had a significant impact on finances and relationships. In addition, it has also been shown that this financial stress may impact both couple and family well-being and relationships in a variety of ways [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study also highlights that economic stability of Portuguese citizens weakened during the pandemic of COVID-19 and shows that there is significantly evidence that agreement with the maintenance of the citizens’ economic stability increases with economic stability before the pandemic. These findings are in accordance with those of Andrade et al [ 41 ] that showed that the pandemic has had a significant impact on finances and relationships. In addition, it has also been shown that this financial stress may impact both couple and family well-being and relationships in a variety of ways [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that the pandemic may be portrayed as a stressful situation in the face of the major disruptions in family and working lives, with impacts on the emotional and physical well-being of the citizens (e.g. [ 41 , 44 , 45 ].). COVID-19 and the associated lockdowns and changes in lifestyle have increased stress, and even conflict, within relationships, have cause financial stress, reduction in healthcare access, and many other changes that impact life satisfaction and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Our cross-sectional study “Family amid COVID-19 survey 1” (FamCov-1) in May 2020 showed that Hong Kong adults who perceived harms rather than benefits from the pandemic reported low levels of happiness ( 7 ). However, previous studies have mainly focused on factors at the individual level, overlooking the importance of family, which serves as the immediate setting for individuals to shape and develop their cognitions and emotions ( 8 , 9 ), particularly when family members are confined at home during the pandemic ( 10 ). Moreover, it is unclear about the potential mediator and moderator underlying the associations between individual and family factors and psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, much research has shown high levels of depression, as in the case of older people in residential care in Israel [ 60 ], New Zealanders of European origin [ 104 ], in Malaysia [ 105 ], and in the US [ 106 ]. Depression has also been reported in the older-adult population in community-dwelling [ 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, women reported a higher number of diseases and medication intake than men ( p -value ≤ 0.05). In the family-dwelling population, older women have been known to be more housebound than men [ 107 ], derived from their greater commitment to household and caregiving activities [ 117 ]. In relation to marital status, being single or widowed increased the likelihood of having a low rating with all residential environment elements (model 3).…”
Section: Discussionmentioning
confidence: 99%